SOCIAL SKILLS AMONG GIFTED AND TALENTED STUDENTS IN MALAYSIA (Proceedings of International Conference on Special Education, 2015)
This research is to explore the social skills among gifted and talented students in Malaysia. This study is to identify whether the social skills among the gifted and talented students in Malaysia is equal to other gifted and talented students. This research involved 220 samples (87 male, 133 female) from Pusat PERMATApintarTM Negara, Universiti Kebangsaan Malaysia encompasses students in Education Program and ASASIpintar Program. The instrument used to measure the social skills is Malaysian Emotional Quotient Inventory (MEQI) which examined the social skills level in eight factors. The finding showed, gifted and talented students in Malaysia have social skills in themselves. The implication of the study will also discuss in this research